International Collaborative Experiences to Design Areas Prone to Flood: Intervention in the Southern part of Resistencia (Argentina) - Valeria Schneider; María José Roibón; María Victoria Valenzuela; Julio Borges Nogueira (International Journal of Built Environment and Scientific Research, 2021)
The Brian A. Thomson Institute of Urban and Regional Planning of the Faculty of Architecture and Urbanism of the UNNE (Argentina) and the Jurusan Arsitektur Fakultas Teknik, Faculty of Engineering, Universitas Muhammadiyah Jakarta (Indonesia), have been developing joint activities within approved projects since 2015, as part of a framework of International Cooperation Agreement. Faced with the global context situation due to the Covid19 pandemic, where virtual activities flourished, it was considered an opportunity to bring together teams from both institutions in a joint activity. Therefore, an "International Workshop on Landscape 2020" was formulated to find better design schemes to mitigate the flood in the Southern area of Resistencia city in Argentina by implementing sustainable strategies to design flooding parks for recreational and absorbent purposes. With highly satisfactory outcomes prepared jointly by groups of students from both geographies, with the follow-up of coordinating Lecturers (Facilitators) and the participation of Keynote Speakers, a compendium was made for the formal transfer to the Local authorities, fostering the link between the academic spheres and society through a university extension mechanism. This article aimed to describe the collaborative work process, analyze the implemented methodologies, and lecturers and students' perceptions of this experience.